Glycinergic Neurotransmission: A Potent Regulator of Embryonic Motor Neuron Dendritic Morphology and Synaptic Plasticity - Fogarty, Matthew J. (J Neurosci, 2016)
Emerging evidence suggests that central synaptic inputs onto motor neurons (MNs) play an important role in developmental regulation of the final number of MNs and their muscle innervation for a particular motor pool. Here, we describe the effect of genetic deletion of glycinergic neurotransmission on single MN structure and on functional excitatory and inhibitory inputs to MNs. We measured synaptic currents in E18.5 hypoglossal MNs from brain slices using whole-cell patch-clamp recording, followed by dye-filling these same cells with Neurobiotin, to define their morphology by high-resolution confocal imaging and 3D reconstruction. We show that hypoglossal MNs of mice lacking gephyrin display increased dendritic arbor length and branching, increased spiny processes, decreased inhibitory neurotransmission, and increased excitatory neurotransmission. These findings suggest that central glycinergic synaptic activity plays a vital role in regulating MN morphology and glutamatergic central synaptic inputs during late embryonic development. SIGNIFICANCE STATEMENT MNs within the brainstem and spinal cord are responsible for integrating a diverse array of synaptic inputs into discrete contractions of skeletal muscle to achieve coordinated behaviors, such as breathing, vocalization, and locomotion. The last trimester in utero is critical in neuromotor development, as this is when central and peripheral synaptic connections are made onto and from MNs. At this time-point, using transgenic mice with negligible glycinergic postsynaptic responses, we show that this deficiency leads to abnormally high excitatory neurotransmission and alters the dendritic architecture responsible for coherently integrating these inputs. This study compliments the emerging concept that neurodevelopmental disorders (including autism, epilepsy, and amyotrophic lateral sclerosis) are underpinned by synaptic dysfunction and therefore will be useful to neuroscientists and neurologists alike.